Active vibration isolation system for free space optic communication: virtual prototyping using LabVIEW-SolidWorks - A. Rahim, Syazwani; Abdul Muthalif, Asan Gani; Turahim, Khairiah K. (Trans Tech Publications Ltd., Switzerland, 2012)
In Free Space Optic (FSO) communication, the alignment between transmitter and receiver telescope is very important. The line of sight of their optics must be aligned during the entire communication time; this is crutial in large distance data transmission. One of the factors that causes misalignment is vibration, either at the transmitter or the receiver. In this work, active vibration isolation (AVI) system is designed and developed to tackle this issue. An AVI system isolates FSO devices from direct disturbances or ground vibrations. The LQR controller is proposed and implimented with LabVIEW. A mathematical model of the isolator is derived and the prototype model of the AVI system is designed in SolidWorks. This prototype model is integrated with LabVIEW software to perform virtual prototyping